Public Diplomacy in Slovakia: Past and Present - A. N. Marchukov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In academic discourse, public diplomacy is often regarded as an instrument of foreign policy most suitable for small states, which enables them to compensate for the lack of military and economic capabilities. Paradoxically enough, studies on public diplomacy usually focus on the activities of the leading actors of world politics. However, it is exactly the case of small states that, according to the author, allows better understanding of the role of public diplomacy in the contemporary foreign policy agenda. The author examines the evolution of the Slovak public diplomacy, and distinguishes two stages in it. The firststage (from 1993 to 2004) was characterized by the establishment and consolidation of the Slovak system of public diplomacy, aimed primarily at promoting the main goal of the government — the country’s integration into the European Union. By means of advocacy and cultural diplomacy, in particular through the system of Slovak Institutes, Slovakia tried to convince politicians, journalists, members of the academic and business communities, and non-governmental organization activists in Europe that the country was ready to join the EU. During the second stage (from 2005 to the present day) a national branding, aimed at promoting a positive image of the country has come to play (along with cultural diplomacy) one of the key roles within the Slovak public diplomacy. It was at this time that the government initiated the National Scholarship Program of the Slovak Republic and launched an information campaign with the slogan ‘Slovakia is a Good Idea’, which had made a significant contribution to the dissemination of accurate information about the country and strengthened relations with the neighboring states and trade partners. The author concludes that in nearly three decades Slovakia has managed to establish a modern competitive system of public diplomacy, which possesses the following characteristics: a high level of coordination between the key actors, a wide range of working methods, and an effective dialogue with the people of the country on the main foreign policy objectives (domestic public diplomacy).